The Effect of Aggregate Characteristics in the Waisikabiri River in Lilibooi on the Bending Pavement of the Highway; A Quantitative Study - Mussa Batkormbawa (Takaza Innovatix Labs Ltd., 2026)
This study aims to analyze the effect of flaky and elongated aggregate characteristics from the Waisikabiri Quarry, Lilibooi Village, Ambon Island, on the performance of flexible pavement mixtures using the Asphalt Concrete-Wearing Course (AC-WC) method. The research employed a quantitative experimental approach through laboratory testing based on the Bina Marga 2010 Revision 3 Division 6 specifications. The materials used consisted of coarse aggregates, fine aggregates, asphalt binder penetration grade 60/70, and Portland cement as filler. The tests conducted included aggregate characteristic tests, asphalt characteristic tests, gradation analysis, and Marshall tests to determine stability, flow, VIM, VMA, and VFB values. The results are expected to provide information regarding the feasibility of using flaky and elongated aggregates in asphalt mixtures and their influence on Marshall stability. This research is expected to contribute to the selection of suitable aggregate materials for durable and high-quality road pavement construction.